Attitudes and knowledge of urethral catheters: a targeted educational intervention. (18th May 2016) - Cohen, Andrew; Nottingham, Charles; Packiam, Vignesh; Jaskowiak, Nora; Gundeti, Mohan
Abstract : Objective: To assess the training of medical students and their confidence in urethral catheter placement, given growing evidence of unnecessary urology consults and iatrogenic injury. Subjects and Methods: A third‐year medical school class was queried about their attitudes and knowledge of catheter placement before and after the Clinical Biennium. The Clinical Biennium introduces hands‐on skills prior to clinical clerkships. Urethral catheterisation is one of the skill stations that students rotate through, and urology residents provide a didactic session and supervised simulation. Confidence was self‐rated regarding catheter technique, knowledge, troubleshooting, and comfort with placement in the same and opposite gender. Factual questions were posed about proper insertion and malfunctioning catheters. Results: In all, 92 students participated in the initial survey, 41% female and 59% male, and 87% of the students had never placed a catheter. Students desired high confidence in catheter skills (4.4/5). There were no significant differences in responses for those with a desire to pursue urology vs other specialties, or procedural fields compared with non‐procedural fields. Prior independent learning was reported by 38% of students and was a predictor for increased confidence across all domains ( P < 0.05). In all, 16.7% of students initially identified proper male urethral insertion distance, which improved to 95.6% after the session. Student interest in urology modestly increased after the educational session ( P = 0.028). At 3–6 months follow‐up, students had performed a median (interquartile range) of 4 (2–7) urethral catheter placements, and 74.2% of students rated training useful or extremely useful. Indeed, 54.8% desired more instruction. Knowledge assessment indicated that 93% of students retained comprehension of proper male urethral insertion distance. Clinical Foley training rarely contradicted instruction from the Clinical Biennium (6.5%). At all time‐points, medical student knowledge for troubleshooting catheters was low. Conclusions: Medical students strive for high confidence in urethral catheter placement. Prior targeted education improves confidence and knowledge. Together with clinical experience, these effects are durable up to 6 months.